Socio-Demographic Characteristics of COVID-19 Vaccine Recipients in Kwara State, North Central Nigeria - Al-Mustapha, Ahmad Ibrahim; Abubakar, Musa Imam; Oyewo, Muftau; Esighetti, Rita Enyam; Ogundijo, Oluwaseun Adeolu; Bolanle, Lukman Dele; Fakayode, Oluwatosin Enoch; Olugbon, Abdullateef Saliman; Oguntoye, Michael; Elelu, Nusirat (Frontiers in Public Health, 2022)
Understanding key socio-demographic variables of COVID-19 vaccine recipients is crucial to improving its acceptance and Nigeria’s COVID-19 control strategy. The survey was conducted as a non-probability cross-sectional survey of 2,936 COVID-19 vaccine recipients in Kwara State. Our findings revealed that 74% (n=2,161) of the vaccine recipients were older than 40 years. Forty percent (n=1,180) of the vaccine recipients earned a monthly income greater than 100,000 Naira . Most of the vaccine recipients (64%, n=1,880) had tertiary education while 15% (n=440) of them had no formal education. Almost half of the recipients (47%) were government employees and 28.8% (n=846) of them had health-related backgrounds. Only 17% (n=499) of the vaccine recipients have been screened for the SARS-CoV-2 of which 21% of them tested positive. Only 47% (n=1,378) had been fully immunized. The prevalence of confirmed COVID-19 cases among COVID-19 vaccine recipients in Kwara State was 3.6%. The most recurrent AEFI among vaccine recipients were fever (14%), pain at injection site (47%), headache (19%), and body weakness (9%). The need to protect themselves from the deadly virus was the main reason that prompted people to voluntarily accept the COVID-19 vaccine. There is a high level of COVID-19 vaccine acceptance among respondents across all social classes including those with no formal education, those with very low monthly income (